Using Artificial Intelligence (AI) to Improve EFL Students’ Writing Skill - Rizky Vita Losi; Eka Putra Putra; Nurbaiti Ali; Adinda Silvana Dewi (International Journal of English and Applied Linguistics (IJEAL), 2024)
When encouraged to write, students struggle to explain the idea in words. Writing skills force EFL students to use their imaginations to tell narratives or express opinions. In order to include modern technology into English language instruction, innovative approaches, materials, tools, frameworks, and procedures must be used. Digital writing tools powered by artificial intelligence (AI) have been shown through empirical studies to enhance students' written English competence. Specific technical instruments that could enhance students' writing are part of the use of AI and technology. This study used a library research methodology. Journals, books, papers, library research, theses, and proceeding journals were the sources of the information. The review claims that students may write academically in English more quickly and accurately by using a range of AI and technological tools. However, it becomes essential to integrate technology tools with the actual written skills of learners in order to effectively communicate the ideas. The purpose of tools is to assist, simplify tasks, and impart new knowledge to enable users write more academic English. In the end, by utilizing AI and technology, students can create academic English writing compositions that could help society as a whole while also developing their self-awareness, self-learning, and self-confidence.